Bi Functional Manganese-Pyridine 2, 6 Dicarboxylic Acid Metal Organic Frameworks with Reduced Graphene Oxide as an Electroactive Material for Energy Storage and Water Splitting Applications. Issue 3 (10th March 2023) - Rajasekaran, Sruthi; Reghunath, B. Shalini; Devi K. R., Sunaja; Saravanakumar, B.; William, J. Johnson; Pinheiro, Dephan
Abstract : In recent years, metal organic frameworks (MOFs) with porous carbon materials have significantly improved the design and engineering of high performance electrode materials and have found applications in energy storage devices. This study explores the supercapacitor and electrocatalytic water splitting applications of Mn-MOF/reduced graphene oxide (rGO) composite synthesized via a hydrothermal technique using pyridine 2, 6 dicarboxylic acid as a linker. Mn-MOF/rGO exhibits a specific capacitance of 428.28 F g −1 with a rate capability of 83.7% and high cyclic stability. The oxygen evolution reaction of the composite is evaluated using linear sweep voltammetry, and the overpotential is calculated to be 400 mV. Our primary goal is to investigate the effect of rGO on the electrochemical response of MOF. The dielectrode (Mn-MOF/rGO) electrolysis system exhibits long-run stability with a low cell potential of 1.8 V, indicating its prospective application as an excellent water electrolyzer. The combination of Mn-MOF with rGO helps in increasing the number of active sites, thereby improving its electronic conductivity by enhancing the electron transfer rate. The outstanding electrochemical behaviour of Mn-MOF/rGO paves the way for the use of rGO-incorporated Mn-MOF in bifunctional applications as energy-generating and storage devices.